Rigid π-extended triptycenes via a hexaketone precursor - Kohl, Bernd; Rominger, Frank; Mastalerz, Michael (Organic letters, 2014)
A high-yielding synthesis of a rigid hexaketone is presented that can be transformed into π-extended D3h-symmetric triptycene derivatives with high internal molecular free volumes (IMFVs). The products show excellent photophysical properties combined with high specific surface areas.